Protocolo para la Propagación Sexual del Árbol de la Quina Cinchona officinalis L. en Vivero - Marcelo Bazán, Fátima Elizabeth; Baselly Villanueva, Juan Rodrigo; Mantilla Chávez, Walter; Ramos Cabanillas, Janny Yessenia (Instituto Nacional de Innovación Agraria, 2022)
44 páginas